Long-Distance Repression by Human Silencers: Chromatin Interactions and Phase Separation in Silencers - Ying Zhang; Yi Xiang See; Vinay Tergaonkar; Melissa Jane Fullwood (Cells, 2022)
Three-dimensional genome organization represents an additional layer in the epigenetic regulation of gene expression. Active transcription controlled by enhancers or super-enhancers has been extensively studied. Enhancers or super-enhancers can recruit activators or co-activators to activate target gene expression through long-range chromatin interactions. Chromatin interactions and phase separation play important roles in terms of enhancer or super-enhancer functioning. Silencers are another major type of cis-regulatory element that can mediate gene regulation by turning off or reducing gene expression. However, compared to active transcription, silencer studies are still in their infancy. This review covers the current knowledge of human silencers, especially the roles of chromatin interactions and phase separation in silencers. This review also proposes future directions for human silencer studies.